Champion and audit and feedback strategy fidelity and their relationship to depression intervention fidelity: A mixed method study - Christopher F. Akiba; Vivian F. Go; Byron J. Powell; Kate Muessig; Carol Golin; Josée M. Dussault; Chifundo C. Zimba; Maureen Matewere; MacDonald Mbota; Annie Thom; Cecilia Masa; Jullita K. Malava; et al. (Elsevier, 2023)
Background: Globally, mental health disorders rank as the greatest cause of disability. Low and middle-income countries (LMICs) hold a disproportionate share of the mental health burden, especially as it pertains to depression. Depression is highly prevalent among those with non-communicable diseases (NCDs), creating a barrier to successful treatment. While some treatments have proven efficacy in LMIC settings, wide dissemination is challenged by multiple factors, leading researchers to call for implementation strategies to overcome barriers to care provision. However, implementation strategies are often not well defined or documented, challenging the interpretation of study results and the uptake and replication of strategies in practice settings. Assessing implementation strategy fidelity (ISF), or the extent to which a strategy was implemented as designed, overcomes these challenges. This study assessed fidelity of two implementation strategies (a 'basic' champion strategy and an 'enhanced' champion ​+ ​audit and feedback strategy) to improve the integration of a depression intervention, measurement based care (MBC), at 10 NCD clinics in Malawi. The primary goal of this study was to assess the relationship between the implementation strategies and MBC fidelity using a mixed methods approach. Methods: We developed a theory-informed mixed methods fidelity assessment that first combined an implementation strategy specification technique with a fidelity framework. We then created corresponding fidelity indicators to strategy components. Clinical process data and one-on-one in-depth interviews with 45 staff members at 6 clinics were utilized as data sources. Our final analysis used descriptive statistics, reflexive-thematic analysis (RTA), data merging, and triangulation to examine the relationship between ISF and MBC intervention fidelity. Results: Our mixed methods analysis revealed how ISF may moderate the relationship between the strategies and MBC fidelity. Leadership engagement and implementation climate were critical for clinics to overcome implementation barriers and preserve implementation strategy and MBC fidelity. Descriptive statistics determined champion strategy fidelity to range from 61 to 93% across the 10 clinics. Fidelity to the audit and feedback strategy ranged from 82 to 91% across the 5 clinics assigned to that condition. MBC fidelity ranged from 54 to 95% across all clinics. Although correlations between ISF and MBC fidelity were not statistically significant due to the sample of 10 clinics, associations were in the expected direction and of moderate effect size. A coefficient for shared depression screening among clinicians had greater face validity compared to depression screening coverage and functioned as a proximal indicator of implementation strategy success. Conclusion: Fidelity to the basic and enhanced strategies varied by site and were influenced by leadership engagement and implementation climate. Champion strategies may benefit from the addition of leadership strategies to help address implementation barriers outside the purview of champions. ISF may moderate the relationship between strategies and implementation outcomes.